(untitled) (Bangladesh Journal of Botany, 2018)
In the present study, chemical compositions of essential oils from seeds and leaves of laurel (Laurus nobilis L.) were evaluated using GC-GC/MS system. Sixty nine different compounds were identified constituting 86.7% of the total oil from the seed, while 76 compounds were determined, constituting 95.8% of the total oil extracted from the leaves. The major compounds of essential oil from laurel seeds included eucalyptol (17.2%), α-terpinyl acetate (9.0%), caryophyllene oxide (6.1%), spathulenol (5.0%) and methyl eugenol (4.2%), constituting 41.5% of the total oil. However, eucalyptol (18.0%), α-terpinyl acetate (13.1%), sabinene (7.8%), α-pinene (4.5%), 2 (4-methoxyphenyl)-N,N,2-trimethyl-1-pyrroline (4.4%) were identified as the major compounds in the oil from laurel leaves, constituting 47.8% of the total oil. Eucalyptol and α- terpinyl acetate, belonging to monoterpenoids, were determined in the highest concentrations within both oils. However, the other principle compounds differ between the two volatile oils.